Hospital Administration as Factors Associated with Patient Satisfaction: A Meta-Analysis - Maesaroh, Siti; Fauziah, Ani Nur; Putri, Imram Radne Rimba; Ulhaq, Muhammad Zia; Rokhmatun, Puji Nur; Zamani, Ahmad; Atmojo, Joko Tri; Sunaryanti, Sri Sayekti Heni; Widiyanto, Aris (Journal of Health Policy and Management, 2022)
Background: Maintaining hospital quality is the most important thing to consider in hospital service indicators. Patient satisfaction is one of the important factors in maintaining hospital quality. This study aimed to analyzed the associated between hospital administration with patient satisfaction.Subjects and Method: This study is a meta-analysis with PICO, population: patients. Intervention: good hospital administration. Comparison: poor hospital administration. Outcome: patients’ satisfaction. The articles used in this study were obtained from three databases, namely Google Scholar, Pubmed, and Science Direct. Keywords to search for articles are “Hospital Administration” OR “Good Administration” OR “Hospital Services” AND “Patient Satisfaction” OR “Satisfaction” AND “Multivariate”. Articles included are full-text English from 2009 to 2021. Articles were selected using a PRISMA flow diagram. Articles were analyzed using the Review Manager 5.3 application.Results: A total of 7 cross-sectional study articles from Asia (China), Europe (Germany), and Africa (Ethiophia) were reviewed in the meta-analysis. Based on the results of the analysis, it was found that good hospital administration has the possibility to increase patient satisfaction 3.58 times compared with poor hospital administration (aOR= 3.58; 95% CI= 2.36 to 5.42; p<0.001) and the results were statistically significant.Conclusion: Hospital administration associated with patients statisfaction.Keywords: hospital, hospital administration, patient statisfaction, inpatients.Correspondence: Siti Maesaroh. School of Health Sciences Mamba’ul Ulum Surakarta. Jl. Ringroad Utara, Mojosongo, Jebres, Surakarta, Central Java, Indonesia. Email: maesarohsiti70@gmail.com. Mobile: +62 813-9386-7942.Journal of Health Policy and Management (2022), 07(03): 227-334https://doi.org/10.26911/thejhpm.2022.07.03.07